GLOSA DO WYROKU NSA W WARSZAWIE Z DNIA 11 STYCZNIA 2012 R. II GSK 1365/10 - Jan Szulc (Zeszyty Prawnicze)
a GLOSS ON VERDICT II GSK 1365/10 ISSUED ON 11TH JANUARY 2012 BY THE POLISH SUPREME ADMINISTRATIVE COURT IN WARSAW Summary The verdict in question concerns the possibility of pharmacies providing services which are not specifically defined in the applicable legal regulations, in this case facilities for patients to take their own blood pressure. The fact that the status of pharmacies in the Polish healthcare system has not been fully defined has given rise to a number of practical problems, one of which is the extent of additional services which may be rendered in pharmacies. One of the controversial issues is the list of such services under Pharmaceutical law, and the viability of pharmaceutical care being rendered on the premises in pharmacies. Pharmaceutical care has been described in detail in the professional literature, but it has still not been implemented in Polish law and currently there are no opportunities for its implementation in the pharmacies. Nonetheless sometimes it is invoked for the provision of additional services in pharmacies. Another controversial point is the possibility for the imposition of restrictions on commercial freedom by sub-statutory means, viz. though an executive ordinance. However, under the jurisdiction of the Polish Constitutional Court and according to the professional literature such practices are admissible under certain conditions, e.g. if the relevant statutory act has laid down specific provisions allowing thereof.